IMPLEMENTASI MANAJEMEN PENDIDIKAN DALAM MENINGKATKAN MUTU DAN EFEKTIVITAS PEMBELAJARAN DI SEKOLAH DASAR DI ERA DIGITAL - Hasbullah, Hasbullah (Berajah Journal, 2025)
The development of digital technology has brought about major changes to the education system, including at the primary school level, which forms the foundation for shaping the character and competencies of students. This study aims to analyse the implementation of education management in improving the quality and effectiveness of learning in primary schools in the digital era. The method used is a literature review with a qualitative descriptive approach through the analysis of various scientific sources such as journals, books, and education policies. The results of the study show that the implementation of effective educational management in the digital era must include the functions of planning, organising, implementing, and supervising, integrated with the use of information and communication technology. The headteacher plays an important role as a transformational leader in guiding teachers to be able to innovate and develop digital-based learning. Strengthening adaptive, participatory, and data-based school management has been proven to improve the efficiency of the teaching and learning process, student engagement, and the quality of learning outcomes. Thus, the digitisation of educational management is not only a modernisation strategy but also an important instrument in realising high-quality, effective, and competitive basic education amid dynamic global changes.